2018
DOI: 10.1007/s12185-018-2444-0
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of induction therapy and prolongation of maintenance therapy did not improve the outcome of pediatric Langerhans cell histiocytosis with single-system multifocal bone lesions: results of the Japan Langerhans Cell Histiocytosis Study Group-02 Protocol Study

Abstract: Langerhans cell histiocytosis (LCH) with single-system (SS) multifocal bone (MFB) lesions is rarely fatal, but patients may experience relapses and develop LCH-associated sequelae. To evaluate effect on outcomes of pediatric multifocal LCH, we tested a treatment protocol modified from the Japan Langerhans Cell Histiocytosis Study Group (JLSG)-96 study. We assessed the outcomes of all consecutive newly diagnosed pediatric patients with LCH with SS-MFB lesions who were treated with JLSG-02 protocol in 2002-2009.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 24 publications
0
57
1
Order By: Relevance
“…The JLSG‐96 and ‐02 multicenter, clinical trials for children with multifocal LCH are described in detail elsewhere . The studies were approved by the institutional review board of the Kyoto Prefectural University of Medicine, at which the JLSG registration office is located, and written informed consent was provided by all patients or legal guardians prior to inclusion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The JLSG‐96 and ‐02 multicenter, clinical trials for children with multifocal LCH are described in detail elsewhere . The studies were approved by the institutional review board of the Kyoto Prefectural University of Medicine, at which the JLSG registration office is located, and written informed consent was provided by all patients or legal guardians prior to inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…Multifocal LCH cases are subdivided into two types: single‐system multisite (SS‐m) and multisystem (MS). Previous studies demonstrated excellent overall survival rates in LCH patients treated with the intensive chemotherapy regimens of the Histiocyte Society (LCH‐I, LCH‐II, LCH‐III) or the Japan LCH Study Group (JLSG‐96, JLSG‐02). However, LCH is associated with various permanent consequences, which result in long‐term impairments in quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Many different therapeutic strategies have been used for bone LCH. 1,2 Among less toxic and more effective regimens, indomethacin was found to be an effective analgesic and, subsequently, its effectiveness in reversing the disease process in children with symptomatic bone LCH, at diagnosis, or after reactivation, was demonstrated. [3][4][5] The rationale of its use is based on the mechanism of action of indomethacin, a non-steroidal anti-inflammatory drug that inhibits the cyclooxygenase 1 and 2 enzymes, involved in the arachidonic acid-prostaglandin pathway.…”
Section: Indomethacin Is An Effective Treatment In Adults and Childrementioning
confidence: 99%
“…However, there are still chronic myeloid leukaemia (CML) patients who are sequentially resistant to different TKIs and even worse therapies in BCR-ABL1-positive B cell acute lymphoblastic leukaemia (B-ALL). 1 Ponatinib is the only registered third-generation TKI effective against almost all single BCR-ABL1 kinase domain (KD) mutations, including the gatekeeper T315I. Unfortunately, clinical and in vitro studies have shown that certain compound mutations (CMs, two or more nucleotide substitutions that change one or multiple codons) confer resistance to ponatinib, [2][3][4] but with inconsistent reports.…”
Section: Dynamic Evolution Of Ponatinib-resistant Mutations In Bcr-abmentioning
confidence: 99%
See 1 more Smart Citation